Upaya Meningkatkan Hasil Belajar dan Sikap Kerjasama dengan Menggunakan Model Problem Based and Learning Berbantuan Media Visual pada Siswa Fase D Kelas VII di SMP Negeri 1 Mardingding - Sri Juliana Br Karo; Brigida Intan Printina; Vinsensius Kriswidiatma Tjahja Hernawa (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve learning outcomes and cooperative attitudes between students by using the Problem Based and Learning model assisted by visual media in students of SMP Negeri 1 Mardingding. This research is a classroom action research. This research was conducted at SMP Negeri 1 Mardingding involving 8 Catholic students in the 2024/2025 academic year. Actions are carried out in two learning cycles. Data were collected with observation guidelines, tests in each cycle, and analyzed in a qualitative descriptive manner. Based on the learning outcomes of grade VII students out of 8 students, only 3 people or 33.33% obtained a score above the KKM or completed it. Meanwhile, 5 other students or 66.66% have not finished. Thus, the application of methods that can improve student learning outcomes that can be done is the Problem Based Learning (PBL) method. PBL not only improves cognitive aspects, but also helps students in reflecting on their abilities and limitations.